2011
DOI: 10.1007/s11104-011-0907-7
|View full text |Cite
|
Sign up to set email alerts
|

The chemical nature of P accumulation in agricultural soils—implications for fertiliser management and design: an Australian perspective

Abstract: Many agricultural soils worldwide in their natural state are deficient in phosphorus (P), and the production of healthy agricultural crops has required the regular addition of P fertilisers. In cropping systems, P accumulates almost predominantly in inorganic forms in soil, associated with aluminium, calcium and iron. In pasture soils, P accumulates in both inorganic and organic forms, but the chemical nature of much organic P is still unresolved. The P use efficiency (PUE) of fertilisers is generally low in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
198
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(208 citation statements)
references
References 145 publications
(175 reference statements)
5
198
1
4
Order By: Relevance
“…The physicochemical properties reported in Table 1 were selected because these are the properties most often reported as affecting the sorption properties of soils (Hinsinger 2001;Laboski and Lamb 2004;Allen and Mallarino 2006;Devau et al, 2011;McLaughlin et al, 2011;Eriksson et al, 2015). For example, soil pH and clay content are reported to have a strong relationship with the P sorption capacity of soils, as they are related to the amount of Al, Fe, and Ca present in the soil solution (Violante and Pigna, 2002;Devau et al, 2011;Bair et al, 2014;Eriksson et al, 2015;Gérard, 2016).…”
Section: Selected Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical properties reported in Table 1 were selected because these are the properties most often reported as affecting the sorption properties of soils (Hinsinger 2001;Laboski and Lamb 2004;Allen and Mallarino 2006;Devau et al, 2011;McLaughlin et al, 2011;Eriksson et al, 2015). For example, soil pH and clay content are reported to have a strong relationship with the P sorption capacity of soils, as they are related to the amount of Al, Fe, and Ca present in the soil solution (Violante and Pigna, 2002;Devau et al, 2011;Bair et al, 2014;Eriksson et al, 2015;Gérard, 2016).…”
Section: Selected Soil Propertiesmentioning
confidence: 99%
“…The solubility of phosphorus in soil is controlled by several factors, including how much P is originally adsorbed in the soil, how much P is precipitated in the soil, the soil pH, clay mineralogy, organic matter content, what types of minerals were formed during P precipitation, and the concentration of Ca, Al, Fe, and other cations in solution (Delgado and Torrent 2000;Violante and Pigna, 2002;Shigaki and Sharpley 2011;Weng et al, 2012;Eriksson et al, 2015;Gérard, 2016). McLaughlin et al (2011) has shown that the amount of Ca, Al, and Fe, in the soil solution controls P solubility and mobility from the inside of the fertilizer granule to the surrounding soil particles. In alkaline soils, P will primarily bind to Ca; in weathered acidic soils, P will pri- …”
mentioning
confidence: 99%
“…The widespread realization that improvements in P nutrition are crucial to the future need to raise global agricultural production has resulted in several recent reviews that have explored these different opportunities (Hinsinger 2001, McNeill and Penfold 2009, Richardson et al 2009, Ryan et al 2009, McLaughlin et al 2011, Simpson et al 2011, Rowe et al 2016.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that most soils worldwide are rich in total inorganic and organic phosphorus, but are very poor in soluble and available P forms (McLaughlin et al 2011). This is, in part, due to its precipitation, surface runoff, and adsorption onto soil minerals especially those rich in calcium and magnesium or iron and aluminum in alkaline and acidic soils, respectively (Richardson et al 2009;McLaughlin et al 2011). In general, available P concentration in soil solution range from 0.001 to 0.2 µg/mL representing only about 0.1% of total soil P (Brady and Weil 2002).…”
Section: Introductionmentioning
confidence: 99%